1995
DOI: 10.1143/jjap.34.l1675
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Anisotropic Ablation and Deposition of Polytetrafluoroethylene Using Synchrotron Radiation Process

Abstract: Both anisotropic ablation and thin film formation of polytetrafluoroethylene (PTFE) were successfully demonstrated using synchrotron radiation (SR) irradiation of PTFE, that is, the SR ablation process. Anisotropic ablation by the SR irradiation was performed at an extremely high rate of 3500 µm/min at a PTFE target temperature of 200° C. Moreover, a PTFE thin film was formed at a high rate of 2.6 µm/min using SR ablation of PTFE. The chemical structure of the deposited film was similar to that of the PTFE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Recently, it has been determined that synchrotron radiation (SR) can facilitate micron-scale etching of PTFE at a very rapid rate. [2][3][4][5][6][7] Recently, several studies have reported on the microetching of PTFE substrates using SR irradiation. Zhang et al [2] have demonstrated the direct microetching of PTFE substrates with a high aspect ratio using an SR-induced ablation reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been determined that synchrotron radiation (SR) can facilitate micron-scale etching of PTFE at a very rapid rate. [2][3][4][5][6][7] Recently, several studies have reported on the microetching of PTFE substrates using SR irradiation. Zhang et al [2] have demonstrated the direct microetching of PTFE substrates with a high aspect ratio using an SR-induced ablation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [2] have demonstrated the direct microetching of PTFE substrates with a high aspect ratio using an SR-induced ablation reaction. Inayoshi et al [3] have performed the anisotropic micromachining of PTFE with patterned holes that were 2 m in diameter. They have also determined the etching mechanism of PTFE under SR by using Fourier transform infrared absorption spectroscopy (FT-IR) analysis and in situ quadruple mass spectroscopy (QMS).…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments were performed using synchrotron sources, investigating the influence of low energy density EUV radiation on polymers like PMMA [11][12][13] or PTFE [14][15][16]. In the last years also table-top EUV sources [17,18] were used for structuring of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Ejected material can be collected on a chosen substrate so that high-quality thin films are produced. 4,7,8,14,15 X-ray ablation has also been investigated for making durability assessments of materials suggested for ICF reactor first walls [18][19][20] and optical elements exposed to intense XUV/SXR radiation in a laser-plasma interaction chamber. [21][22][23] XUV/SXR ablation of metals has also been used for determination of the energy content of intense radiation pulses emitted from a hot dense plasma.…”
Section: Introductionmentioning
confidence: 99%